Tingkat Kepemilikan Manajerial dan Nilai Perusahaan: Bukti Empiris pada Perusahaan Publik di Indonesia - Henry Henry; Hamin Hamin (Jurnal Riset Manajemen dan Bisnis, 2006)
Initial analyses using panel data for none intercept model show a positive and significant effect of low level of managerial ownership on firm value ond negative and significant effect of high level of managerial ownership on firm value. This conclusion is dffirent when unobserved firm heterogeneity controlled using firm fixed effects model. Thefixed effects analyses suggest that managerial ownership doesn't have significant effect on firm value. The 2SLS analyses show that both managerial ownership and firm value are jointly endogenous. Managerial ownership has positively impacts on firm value, on higher firm value, on the other hand, inspires larger managerial ownershipKeywords: Managerial Ownership, Firm Yalue, Tobin's Q